The Influence of Liquid Organic Fertilizer from Pineapple Peel Waste and Chicken Manure Compost on the Growth and Production of Purple Eggplant (Solanum melongena) - Anjas Irmawan; Desi Sri Pasca Sari Sembiring; Hanifah Mutia Zaida Ningrum Amrul (Universitas Labuhanbatu, 2025)
Eggplant (Solanum melongena L.) is a widely recognized food source among all segments of society. It has become one of the most favored dishes across various groups. The demand for purple eggplant continues to rise; however, this increase in demand is not accompanied by a corresponding rise in production levels. The Factorial Randomized Block Design with two factors and three replications is used in this study. The observation parameters in this study include stem diameter (mm), plant height (cm), fruit length (cm), number of fruits per planting (fruits), number of fruits per plot (fruits), weight of fruits per planting (g), and weight of fruits per plot. The study's findings demonstrated that using fertilizer made from chicken manure significantly impacted the following parameters: fruit length (cm) in the K3 treatment were 20.09 cm and the S3 treatment of pineaple peel waste were 18.83 cm, fruit weight per plant (g) in the K3 treatment were 782.11 g, and S3 treatment were 735.86 g and had no discernible impact on the following parameters: fruit weight per plot (g) in the K3 treatment of chicken manure fertiliser were 781.27 g and the S3 treatment of pineapple peel waste were 7.14 g; number of fruits per plant (fruit) in the K3 treatment of chicken manure fertiliser were 7.46 fruit and the S3 treatment of pineapple skin waste were 7.18 fruit. There is no effect of pineapple peel waste LOF on all parameters